Belt and Road Initiatives & Mongolia: Expert Survey Results - Khatanbold Oidov (The Mongolian Journal of International Affairs)
Since 1990, Mongolia has been moving from a planned economy to a market economy for more than 30 years, revolutionizing the social order and adopting democratic methods. Over the past few years, Mongolia's social, economic and political development studies have produced specific assessments and conclusions. These articles explore Mongolia's development, characteristics, participation in the Belt and Road Initiative launched by the People's Republic of China, its benefits, its impact on the present state of Mongolia's society and the obstacles it faces. The paper presents the results of research into four main groups: common reasons, cause-effect, solution-effect and conclusions.